EKSISTENSI MADRASAH DALAM SISTEM PENDIDIKAN NASIONAL - Sultan; Ina Damayanti (El-Fata: Journal of Sharia Economics and Islamic Education, 2022)
The research aims to analyze madrasah in the national education system. The type of research used is library research, with a research approach namely the sociological approach to education and the normative theological approach. The results of the study show that along with the development and expansion of Islam, madrasas as Islamic educational institutions began to be established and developed in the Islamic world around the 5th-6th century H or 11-12th centuries. So madrasas need serious renewal to overcome and educate the nation's children who are not only fixated on old-style study benches but are also able to compete in a world full of "modern" progress. The influence of the ideas of renewal that developed in the Islamic world and the national awakening of the Indonesian nation, little by little general subjects entered the madrasah curriculum. The quality of education in madrasas must continuously be improved so that it is of high quality so that it is able to contribute in preparing quality human resources as a national asset that can contribute to national development so that it becomes a nation that has high competitiveness at the international level.